Patterns of ROS Accumulation in the Stigmas of Angiosperms and Visions into Their Multi-Functionality in Plant Reproduction - Zafra, Adoración; Rejón, Juan D.; Hiscock, Simon J.; Alché, Juan de Dios (Frontiers in Plant Science, 2016)
Accumulation of reactive oxygen species (ROS) in the stigma of several plant species has been investigated. Four developmental stages (unopened flower buds, recently opened flowers, dehiscent anthers and flowers after fertilization) were analyzed by confocal laser scanning microscopy using the ROS-specific probe DCFH2-DA. In all plants scrutinized, the presence of ROS in the stigmas was detected at higher levels during those developmental phases considered “receptive” to pollen interaction. In addition, these molecules were also present at early (unopened flower) or later (post-fertilization) stages, by following differential patterns depending on the different species. The biological significance of the presence ROS may differ between these stages, including defense functions, signaling and senescence. Pollen-stigma signaling is likely involved in the different mechanisms of self-incompatibility in these plants. The study also register a general decrease in the presence of ROS in the stigmas upon pollination, when NO is supposedly produced in an active manner by pollen grains. Finally, the distribution of ROS in primitive Angiosperms of the genus Magnolia was determined. The production of such chemical species in these plants was several orders of magnitude higher than in the remaining species evoking a massive displacement towards the defense function. This might indicate that signaling functions of ROS/NO in the stigma evolved later, as fine tune likely involved in specialized interactions like self-incompatibility.